The Great Chinese Inequality Turnaround - Ravi Kanbur; Yue Wang; Xiaobo Zhang (Institute of Labor Economics (IZA), 2017)
This paper argues that after a quarter century of sharp and sustained increase, Chinese inequality is now plateauing and even turning down. The argument is made using a range of data sources and a range of measures and perspectives on inequality. The evolution of inequality is further examined through decomposition by income source and population subgroups. Preliminary explanations are provided for these trends in terms of shifts in policy and structural transformation of the Chinese economy. The narrative on Chinese inequality now needs to focus on the reasons for this great turnaround.
Keywords: D31; D63; O15; O53; 330; Chinese inequality turnaround; inequality data; inequality trends; inequality and structural transformation; harmonious development and government policy